Cover Picture: Ultrathin Coating of Confined Pt Nanocatalysts by Atomic Layer Deposition for Enhanced Catalytic Performance in Hydrogenation Reactions (Chem. Eur. J. 25/2016). Issue 25 (23rd May 2016) - Wang, Meihua; Gao, Zhe; Zhang, Bin; Yang, Huimin; Qiao, Yan; Chen, Shuai; Ge, Huibin; Zhang, Jiankang; Qin, Yong
Abstract : A strategy to maximize the metal‐oxide interfaces is proposed by coating confined nanoparticles with an ultrathin oxide layer. The main features of the designed catalyst are: Al2 O3 nanotubes, confined Pt nanoparticles, and ultrathin Al2 O3 coats. These features are represented in the cover‐page graphic. The Pt nanoparticles (yellow ball) were partially embedded in the internal wall of the Al2 O3 nanotubes (gray cylindrical tube) and uniformly coated by the ultrathin Al2 O3 layer (gray ball). More information can be found in the Communication by Z. Gao, Y. Qin et al. onpage 8438 ff.